2005
DOI: 10.1021/es048603o
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tetracycline with Aluminum and Iron Hydrous Oxides

Abstract: The effect of solution chemistry (pH, sorbate-to-sorbent ratio, ionic strength (/)) and reaction time on the sorption of tetracycline to the hydrous oxides of Al (HAO) and Fe (HFO) was examined. Sorption to HAO increased with increasing pH upto pH 7 (no such trend for HFO) above which it decreased at higher pH values for both the hydrous oxides. Experimental results indicate that ligand-promoted dissolution is occurring during tetracycline sorption to these hydrous oxides. Ligand-promoted dissolution was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
250
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(294 citation statements)
references
References 40 publications
26
250
2
2
Order By: Relevance
“…7). Thus, soil solution pH is an important factor influencing the bioavailability of OTC in soil (Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005) and the transport from soil to plant. Time-dependent uptake of OTC by alfalfa showed that there was an equilibrium status of OTC uptake after 4 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Thus, soil solution pH is an important factor influencing the bioavailability of OTC in soil (Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005) and the transport from soil to plant. Time-dependent uptake of OTC by alfalfa showed that there was an equilibrium status of OTC uptake after 4 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Denmark, concentrations of oxytetracycline ranging from 2.5 to 50 mg g À1 in soil and from 33 to 2000 mg g À1 in pig manure have been reported (Loke et al, 2002). The fate of antibiotics, including sorption and fixation, mobility and transport in soil, has been well documented (Tolls, 2001;Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005), whereas knowledge of their toxicity to plants and their uptake and transport into plants is poorly understood (Boxall et al, 2003;Thiele-Bruhn, 2003). The accumulation may or not affect the growth and development of plants; however, the uptake into plants may represent an important exposure pathway of these compounds to humans and other biota.…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding of Cip and tetracycline sorption to soils and soil minerals has revealed similarities in the mechanisms, with both compound classes being sorbed onto aluminosilicate clays either via cation exchange and cation bridging (3,(8)(9)(10) or via surface complexation (4,5,11,12). However, the exact mechanism of surface complexation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the adsorption capacity of the composite did not change significantly with the decrease in surface area. In addition, complex formation of TC with metal and metal oxide present on the surface of the activated carbon might also contribute to their higher adsorption since compounds with carboxylic and phenolic functional groups are capable of forming complexes with metals [14].…”
mentioning
confidence: 99%